Ensuring Data Integrity in Healthcare Records through Hybrid Storage and Blockchain-Backed Audit Trails - Azmiansyah Azmiansyah; Yan Watequlis Syaifudin; Cahya Rahmad; Josafat Pratama Susilo; Triana Fatmawati; Yuri Ariyanto; Pramana Yoga Saputra; Indrazno Siradjuddin; Chandrasena Setiadi (Journal of Evrímata: Engineering and Physics, 2026)
Ensuring the integrity and auditability of Electronic Health Records (EHRs) is critical for patient safety, regulatory compliance, and trust in digital healthcare. Conventional audit mechanisms such as database logs, are inherently mutable and vulnerable to insider tampering, failing to meet stringent requirements for tamper-proof, independently verifiable data provenance. To address this, this paper proposes and implements a hybrid EHR integrity system that combines PostgreSQL for sensitive clinical data storage with a private Hyperledger Fabric blockchain for immutable audit logging. Only lightweight metadata and SHA-256 hashes of records (not full EHRs) are written to the blockchain, preserving privacy while enabling cryptographic verification. Deployed on modest, heterogeneous hardware and featuring a user-friendly web interface with batched audit workflows, the system achieves 100% tamper detection accuracy, 210 ms average write latency, and 45 TPS throughput that demonstrates feasibility for real-world, resource-constrained clinical environments. Our approach delivers strong, scalable data integrity without prohibitive overhead, bridging the gap between regulatory demands and practical healthcare IT deployment.